TINGKAT KESEJAHTERAAN RUMAHTANGGA NELAYAN DI KELURAHAN BERENG BENGKEL KECAMATAN SABANGAU KOTA PALANGKA RAYA - Tri Yuliana Eka Sintha (J-SEA (JOURNAL SOCIO ECONOMIC AGRICULTURAL), 2019)
Purpose of this research are (1) to identify households welfare level of the catch and catchfarming fisherman, (2) to study general problems faced by the catch and catch-farming fisherman households in fisheries development. This research conducted in Bereng Bengkel Village, Sabangau Subdistrict, Palangka Raya City. The site was selected purposively because majority is fisherman. Sample was chosen using purposive sampling. Total sample is 24 fisherman households that consist of 18 catch fisherman households and 6 catch-farming fisherman households. Household’s characteristics that studied are age, education, dependency, secondary job, ethnic, and facility ownership. In the catch fisherman households,the age of households head varies (51-64 years old), majority is primary school graduated, dependency is 4-5 people, minority having various secondary jobs, majority is Dayak tribe, and using 8types of catching-equipments. In the catch-farming fisherman households the age of households head varies and in productive age (31-44) years old, majority is primary school graduates, dependency is between 3–4 people, almost catchfarming fisherman having variety of secondary jobs, majority is Banjar tribe (62%), and using 4 types of catching-equipments. The research shows that majority of the catch fisherman household (83,33%) is not prosperous and the rest (16,67%) is pre-prosperous. It showed by the average Proportion of Food Consumption is 75%. As a contrast in the catchfarming fisherman household, only 33,33% is categorized not prosperous and 66,67% is declared pre-prosperous, that showed by the averages proportion of food consumption is 63%. General problem faced by the catch and catch-farming fisherman households are season and water condition. The season affects the number of catches-fish and water condition affects condition of fish that farmed in the floating fish-cage in the river.